2019
DOI: 10.1016/j.cell.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoid Size Scaling and Intracellular Organization of Translation across Bacteria

Abstract: Supplemental figure legends9 Figure S1. Related to Figure 1. Cell and nucleoid morphology of E. coli cells in different growth 10 media. 11 A. Representative phase contrast and DAPI images of E. coli cells (CJW6324) grown in liquid cultures 12of M9 medium supplemented with the indicated carbon source and other chemicals (CAAT: 0.1% 13 casamino acids and 1 µg/ml thiamine) at 37 °C. For a full description of the growth media, see Table 14 S1. Cell contours (green) were generated using Oufti. 15 B. Bar graph sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
97
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 125 publications
(136 reference statements)
12
97
1
Order By: Relevance
“…), and 4.7 ± 0.05 µm and 2.6 ± 0.05 µm, respectively, for cells grown at 30 ºC. At both temperatures, we found a linear dependence between the nucleoid length and the cell contour length, similar to other studies 16,18 (Fig. 2h).…”
Section: Replisomes Load Near the Middle Of The Cell And Then Move Awsupporting
confidence: 91%
“…), and 4.7 ± 0.05 µm and 2.6 ± 0.05 µm, respectively, for cells grown at 30 ºC. At both temperatures, we found a linear dependence between the nucleoid length and the cell contour length, similar to other studies 16,18 (Fig. 2h).…”
Section: Replisomes Load Near the Middle Of The Cell And Then Move Awsupporting
confidence: 91%
“…1e) for the mostly fast growth rates they analyzed, even though they studied a Salmonella strain. We also extracted cell size data from recent studies by Si et al 3 and Gray et al 18 , and found their data to be consistent with ours (blue and red symbols, Fig. 1f).…”
supporting
confidence: 85%
“…1f). Aside from the average cell size, even the size distributions appear to be indistinguishable for a variety of growth media 18 (Extended Data Fig. 2a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being about a thousand times longer than the dimensions of the cell, it is confined to a fraction of the cytosolic volume, which is referred to as the nucleoid (Wang et al, 2013). The cytosolic volume fraction occupied by a nucleoid has been estimated to be in the range of 20%-75% in E. coli (Woldringh, 2002, Sherratt, 2003, Fisher et al, 2013) and many other bacterial species (Gray et al, 2019). In contrast, when DNA is released from the cell, it expands to a volume that exceeds the cell volume by about 1000-fold (Cunha et al, 2001, Romantsov et al, 2007, Wegner et al, 2012.…”
Section: Introductionmentioning
confidence: 99%